Getting Every Last Drop: How Food Hubs Can Reduce Food Waste and Food Insecurity Through Gleaning - Wilson, Erik. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Tim Griffin.; Keyword: Urban planning.